The Equivalence Principle and the bending of light - Ferraro, Rafael (2003)
The apparent discrepancy between the bending of light predicted by the equivalence principle and its corresponding value in general relativity is resolved by evaluating the deflection of light with respect to a direction that is parallel transported along the ray trajectory in 3-space. In this way the bending predicted by the equivalence principle is fulfilled in general relativity and other alternative metric theories of gravity.